Histology driven systemic therapy of liposarcoma—ready for prime time? - Grethlein, Sara Jo (Translational Gastroenterology and Hepatology, 2018)
Liposarcomas are a subtype of soft tissue sarcomas arising from adipocytes. These mesenchymal tumors have been sub classified into well differentiated liposarcoma (WDLPS), dedifferentiated liposarcoma (DDLPS), myxoid liposarcoma (MLPS) and pleomorphic liposarcoma (PLPS). This article reviews what has been reported regarding the responsiveness of these sarcoma subtypes to traditional and newly developed systemic therapies. The evolution of molecular targets for therapeutic intervention within the distinct histologies is discussed, along with, available evidence regarding the efficacy of novel target directed therapies. Response rates and outcomes for advanced disease therapeutic trials comprises the majority of this information, and where available, data from adjuvant therapy trials is reviewed. Overall survival for patients with advanced liposarcoma treated with systemic therapy is 16.3 months. The article addresses our progress toward the goal of improved liposarcoma outcomes through tailored interventions.